Parches invadidos por Ugni molinae en isla Robinson Crusoe: ¿Hay plantas nativas y endémicas capaces de vivir en ellos? - Alarcón, Diego; López-Sepúlveda, Patricio; Fuentes, Glenda; Montoya, Hellen; Peñailillo, Patricio; Carrasco, Pedro (Gayana Botánica, 2020)
It is unknown if any Juan Fernández native plants may tolerate the aggressive invasion of the introduced shrub Ugni molinae. We found sixteen native species growing within these highly invaded patches. The endemic shrub Gaultheria racemulosa (syn. Pernettya rigida) was the most important species according to vegetation cover in invaded patches, therefore relevant in future control management options.